Embracing Flexibility: Exploring the Impact and Future of Remote Work, Flextime, and the Four-Day Workweek on Productivity and Well-Being - Rinandita Wikansari; Christian Kuswibowo; Dony Firman Santosa; Athira Setira Adil (CV. Media Digital Publikasi Indonesia, 2024)
The study is aimed at trend analysis, adoption, and effects of remote work, flexible schedules, and a four-day work week on performance and employee well-being; it engages in a systematic literature review methodology for data collection on several industries concerning the pros and cons of different flexible employment paradigigms. Remote working has been embraced best in knowledge-intensive industries, where it increases productivity significantly but at the same time enhances the risk of feeling isolated, and flexitime gives a good work-life balance but needs clear demarcations in the use of this flexibility to prevent over-commitment. Though the four-day work week is hardly ever adopted, experimentation has demonstrated its potential for increasing happiness and well-being in workplaces without compromising productivity. Appropriating hybrid models, deploying outcome-based performance measurement, and making training available are recommendations organizations could take on to make the most of flexible working arrangements. Hence, the study argues for personalized approaches to flexibility regarding the work at hand and the demands of the organization to ensure optimum performance and employee satisfaction